Effective properties of undoped and Indium3+-doped tin manganese telluride (Sn1 − xMnxTe) nanoparticles via using a chemical bath deposition route - Patsorn Boon-on (2018)
© 2017 Elsevier B.V. Tin manganese telluride nanoparticles (Sn1−xMnxTe NPs) were first synthesized on a niobium pentoxide (Nb2O5) film using a chemical bath deposition (CBD) route. An individual particle size before and after indium (In3+) doping of ∼70–150 nm was investigated with stoichiometric formation of the SnMnTe phase. Furthermore, a cubic or rocksalt structure of the Sn0.938Mn0.062Te phase was also kept incorporated in the structure. The plotted energy band gaps for undoped and In3+-doped samples were 2.17 and 1.83 eV, respectively. The reduction of photoluminescence (PL) spectra after In3+doping, while the indium dopant acted as a trap state incorporated in Sn1−xMnxTe NPs, showed enhanced charge separation and reduced charge recombination, which resulted in a higher charge density trapped in the conduction band of Nb2O5and was also confirmed by the result of anodic peaks in the cyclic voltammetry. These results suggest new possibilities in optoelectronic and electrochemical devices.